Intra- and inter-group coordination patterns reveal collective behaviors of football players near the scoring zone - Duarte, Ricardo (2013)
This study examined emergent coordination processes in collective patterns of behavior in 3 vs 3 sub-phases of the team sport of asso- ciation football near the scoring zone. We identified coordination tendencies for the centroid (i.e., team center) and surface area (i.e., occupied space) of each sub-group of performers (n = 20 plays). We also compared these kinematic variables at three key moments of play using mixed-model ANOVAs. The centroids demonstrated a strong symmetric relation that described the coordinated attacking/defending actions of performers in this sub-phase of play. Conversely, analysis of the surface area of each team did not reveal a clear coordination pattern between sub- groups. But the difference in the occupied area between the attack- ing and defending sub-groups significantly increased over time. Findings emphasized that major changes in sub-group behaviors occurred just before an assisted pass was made (i.e., leading to a loss of stability in the 3 vs 3 sub-phases).